Ethnobotanical study of medicinal plants used by local communities in Sekerak Subdistrict, Aceh Tamiang, Indonesia - Zidni Ilman Navia; Adi Bejo Suwardi; Baihaqi Baihaqi (Society for Indonesian Biodiversity, 2021)
Abstract. Navia ZI, Suwardi AB, Baihaqi. 2021. Ethnobotanical study of medicinal plants used by local communities in Sekerak Subdistrict, Aceh Tamiang, Indonesia. Biodiversitas 22: 4273-4281. Local communities in Aceh Tamiang have gained a wealth of medicinal knowledge through practice and experience in their long-term battles with the disease. However, because of a lack of written records and rapid economic development, their traditional medicinal knowledge is under threat. This study investigated medicinal plants and related traditional knowledge of local communities in the Sekerak subdistrict, Aceh Taming, Indonesia. Field surveys, plant collections, and interviews with communities were used in this study. The Snowball Sampling technique was used to select 60 informants for the interviews. A total of 46 medicinal plant species belonging to 40 genera and 26 families were used for medicinal purposes by local communities to treat 28 different diseases. The itch, swelling, cough, and nosebleed were the most commonly treated. With a use-value index of 0.98, Tagetes erecta was the most commonly used medicinal plant by local communities. In addition, local communities identified the leaf (50%) as the most widely used plant part and oral administration (65%) as the most common method of administering traditional medicine. Elders have more knowledge of medicinal plants than younger generations, indicating that traditional knowledge is eroding across generations. However, initiatives to promote and conserve medicinal plants must be improved, particularly among the younger generation. This is required to ensure the availability of medicinal plants and the preservation of traditional knowledge in the future.